EPCT-03. A PHASE I TRIAL OF 2-HYDROXYOLEIC ACID IN PEDIATRIC PATIENTS WITH ADVANCED CENTRAL NERVOUS SYSTEM TUMORS. (4th December 2020) - Hanson, Derek
Abstract: 2-hydroxyoleic acid (2-OHOA) is the first potential anti-cancer drug to act by modification of cell membrane lipid content. The agent is a derivative of oleic acid, a naturally occurring component of olive oil. Through its unique mechanism of activating sphingomyelin synthase 1, 2-OHOA targets the membrane lipid composition of cancer cells. These lipid changes alter membrane-dependent signaling cascades, such as the Ras/MAPK pathway, that promote tumor cell proliferation. A comprehensive pre-clinical program has characterized the safety and effects of 2-OHOA across a host of animal models. A European phase I/IIa trial of 2-OHOA in adult patients has shown initial promising results with five refractory high-grade glioma patients demonstrating objective clinical benefit by RANO criteria for six or more months. The drug has been very well-tolerated in adult patients with minimal toxicity. This phase I study is the first pediatric investigation of 2-OHOA and focuses on the treatment of relapsed/refractory pediatric central nervous system (CNS) tumors. The trial consists of a dose-escalation phase in up to 18 patients using a standard "3 + 3" design, followed by an expanded safety cohort of up to 10 patients treated at the maximum tolerated dose to confirm the recommended phase II dose. Due to the promising clinical results in adult neuro-oncology patients and the widespread involvement of the Ras/MAPK pathway and other membrane-dependent signaling cascades in the development of pediatric malignancies, we hypothesize that 2-OHOA may be a safe and effective treatment for pediatric patients with several types of advanced CNS tumors.